Continuing Medical Education. - Cervantes Begazo, René (2015)
Medical education, including the University, is in crisis. One cause is the economic crisis and the shortsightedness of the authorities who see the university as an entity and not economically wasteful investment pays off in the medium and long term. Another cause is the internal struggle for power distribution, ie capturing decision-makers and quotas of power that each group and each ideology claimed.